2014
DOI: 10.1074/jbc.m113.505891
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanism of Prosegment-catalyzed Folding by Solution NMR Spectroscopy

Abstract: Background: Native pepsin can be irreversibly denatured into a thermodynamically stable but non-active form. Results: Prosegment converts the misfolded pepsin to a structure similar to the precursor form of pepsin. Conclusion: Hydrophobic interactions between prosegment and pepsin lower the barrier of pepsin folding toward the native complex. Significance: The mechanism for how the prosegment mediates formation of native pepsin is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…The data presented here ( Fig 3A ) indicate that PS-Rp could be ‘trapped’ for further structural analysis by using a PS with a double mutation (such as PS I17A/F25A ), which would be expected to shift the folding equilibrium from PS I17A/F25A -Np to PS I17A/F25A -Rp. This hypothesis was confirmed recently using 1 H- 15 N TROSY NMR to show that PS I17A/F25A -Rp is structurally very similar to Rp alone [51] .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The data presented here ( Fig 3A ) indicate that PS-Rp could be ‘trapped’ for further structural analysis by using a PS with a double mutation (such as PS I17A/F25A ), which would be expected to shift the folding equilibrium from PS I17A/F25A -Np to PS I17A/F25A -Rp. This hypothesis was confirmed recently using 1 H- 15 N TROSY NMR to show that PS I17A/F25A -Rp is structurally very similar to Rp alone [51] .…”
Section: Discussionsupporting
confidence: 54%
“…Without 100 mM NaCl, no generation of protease activity was observed on a timescale of 0–2 hours (data not shown, and [7] ), indicating that the PS binds Rp yet does not catalyze folding to Np. However, 1 H- 15 N TROSY NMR experiments [51] indicated that PS-Rp does fold to the native complex in the absence of 100 mM NaCl, but over longer timescales of days ( Fig S7 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete polypeptide of PfPMX is synthesized and folded as inactive zymogen (Pfpro-PMX) consisting of a prosegment and a mature domain (Pfm-PMX). The prosegment of PfPMX is longer than its counterpart in vacuolar plasmepsins and other gastric or plant pepsin-like aspartic proteases 12,20,21 . In general, activation of the zymogens of pepsin-like aspartic proteases takes place by removal of the prosegment under acidic conditions.…”
mentioning
confidence: 97%
“…The prosegment of PfPMX is longer than its counterpart in vacuolar plasmepsins and other gastric or plant pepsinlike aspartic proteases. 12,20,21 In general, activation of the zymogens of pepsin-like aspartic proteases takes place by removal of the prosegment under acidic conditions. It is suggested that vacuolar PMs have an auto-activation mechanism wherein the dimeric form is converted to a monomer under acidic conditions due to the disruption of the Tyr-Asp loop at the pro-mature junction, with subsequent unfolding and cleavage of the prosegment by the trans-activation process.…”
mentioning
confidence: 99%